Reducing crime among youth at risk for gang involvement - Thornberry, Terence P. (Criminology & public policy, 2018)
No gang prevention or intervention programs meet the standards for effectiveness promulgated by Blueprints for Healthy Youth Development. This randomized controlled trial of a well‐known program—Functional Family Therapy—that was modified to address the needs of gang‐involved adolescents yields two main findings. First, youth at high risk for gang membership and their families engaged with and successfully completed the program at the same level as low‐gang‐risk youth. Second, the effectiveness results varied by gang‐risk status. For youth at high risk for gang membership, the treatment group had significantly lower recidivism rates at the 18‐month follow‐up as compared with a “treatment as usual” control group. For youth at low risk for gang membership, however, no consistent differences were found between the treated and control groups.